OPTIMIZATION OF EXAMPLE AND ADVICE METHODS IN ISLAMIC EDUCATION: AN ANALYTICAL STUDY OF THE IMPLEMENTATION OF THE VALUES OF THE QUR'AN AND HADITH IN ISLAMIC ELEMENTARY SCHOOL ENVIRONMENT - Saputra, Meidianas; Syafruddin; Rehani; Zulheldi; Yoga Suhendra (International Journal of Multidisciplinary Reseach, 2025)
The implementation of Qur'anic and Hadith values ​​in Islamic education in Islamic Elementary Schools has long been a major concern for educators, particularly through the optimization of exemplary (uswah) and advice (mau'izhah) methods. This study aims to analyze in depth how these methods are applied in an Islamic Elementary School environment, identify the obstacles encountered, and offer recommendations for optimization strategies. Using a qualitative approach with a case study design in one Islamic Elementary School that implements education based on Qur'anic and Hadith values, data were collected through observation, interviews, and documentation studies. The research findings demonstrate the strategic role of exemplary and advice in the internalization of Islamic values, but their implementation faces obstacles such as inconsistency in actor behavior, lack of curriculum integration, and external cultural influences. The implementation of exemplary behavior is reflected in time discipline, congregational worship, and empathetic teacher behavior, while the advice method is carried out both formally and informally, although it is often still less contextual and hampered by external environmental influences. Success was achieved in the aspects of religious habits and strengthening student character. For optimization, this study recommends an integrative model based on the Quran and Hadith, strengthening the role of teachers, and active collaboration between schools and parents. The implications of this research are expected to make a tangible contribution to the formation of Islamic character and improving the quality of Islamic education in elementary schools.